Droughts of the early 19th century (1790–1830) in the northeastern Iberian Peninsula: integration of historical and instrumental data for high-resolution reconstructions of extreme events - J. Barriendos; M. Hernández; S. Gil-Guirado; J. Olcina Cantos; M. Barriendos (Climate of the Past)
Drought represents a prevalent climate risk in the Mediterranean region. In the context of climate change, an increase in both frequency and intensity is anticipated over the next century. In order to effectively manage future scenarios where global warming overlays natural climate variability, a thorough analysis of the nature of droughts prior to the industrial age is crucial. This approach incorporates an extended temporal scale into the study of severe droughts, enabling the identification of low-frequency drought events that occurred before the instrumental period. The objective of this study is to examine the occurrence and magnitude of extreme droughts lasting over a year in the Spanish Mediterranean basin during the early 19th century (1790–1830). To achieve this objective, the research integrates the use of instrumental observations and information derived from historical documentary sources with daily to monthly resolutions (e.g., rogation ceremonies). The findings reveal that drought episodes were more frequent and severe during the early 19th century compared to the late 19th century. Moreover, drought episodes of similar severity were rare throughout the 20th century. Only in the current context of climate change, over the last 2 decades, has a pattern of high drought severity been identified that resembles the severity found during the early 19th century (especially between 1812 and 1825). This study underscores the presence of high variability in drought patterns over the last few centuries, justifying the need for intensified research on drought episodes with high temporal resolution for extended periods.